Effects of an executive function programme (PEFEN) on preschool children: a pilot study - Pérez-Marfil, María Nieves; Fernández-Alcántara, Manuel; López-Benítez, Raúl; Pérez-García, Miguel; Pérez-García, Purificación; Cruz-Quintana, Francisco (SAGE Publications, 2024)
The objective of this study was to test the effectiveness of a programme for the stimulation of executive functions (Programa para la Estimulación de las Funciones Ejecutivas — PEFEN) in preschool children (aged five years) with no pathologies. A total of 40 children participated. They were distributed into two groups (intervention and control groups) and were evaluated at two different moments in time (before and after the intervention) using the Child Neuropsychological Maturity Questionnaire (CUMANIN) and the Behavior Rating Instrument of Executive Function-Preschool (BRIEF-P). The programme’s duration was three months. The results revealed statistically significant differences between both groups in the subscales of psychomotricity, spatial structuring and visual perception of the CUMANIN as well as in the emotional control subscale of BRIEF-P. In conclusion, the intervention group presented higher scores in different neuropsychological domains related to executive functions. This research seems to suggest that programmes such as PEFEN may be useful to improve and stimulate the EFs of normal developing children who do not present any difficulties.
Keywords: Intervention programme; Executive functions; Neuropsychological evaluation; Programa de intervención; Funciones ejecutivas; Evaluación neuropsicológica